Peranan Zakat Mal Pengusaha Ayam Petelur dalam Peningkatan Ekonomi Masyarakat di Jorong Limau Puruik Nagari Limau Purut Kecamatan Kinali - Sonia Astuti; Fawza Rahmat; Maisarah Leli (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This research was conducted in Jorong Limau Puruik, Nagari Limau Purut, Kinali District, with a focus on the role of zakat mal from layer chicken entrepreneurs in improving the community's economy. The formulation of the problem includes the role of zakat mal, the calculation of zakat mal, and the distribution of zakat mal from layer chicken entrepreneurs. This research aims to explain the contribution of zakat in improving the community's economy, calculation methods, and zakat distribution mechanisms. This research uses descriptive qualitative method with field approach. Data were obtained through interviews with zakat recipients (mustahiq), business owners, and laying hen farm employees. Primary data is supported by secondary data from the Limau Purut Nagari Wali Office. The results showed that zakat on laying hens has a significant role in improving the community's economy, both consumptively and productively. Consumptive improvements include the fulfillment of daily needs, education costs, and business capital. Meanwhile, productive improvement occurs when zakat is used as capital for small businesses that develop and have a positive impact on the economy. The calculation of zakat is analogous to trading commodities, with a rate of 2.5% without using the nisab of 85 grams of pure gold, and is paid after haul (one year). Zakat is distributed to mustahiq who are entitled to receive.